Regional productive structure and water pollution: An analysis using the input-output model - Rosa Duarte; Julio Sanchez-Choliz (European Regional Science Association (ERSA), 1998)
The objetive of this paper is to carry out an in-depth study of the structural relations that exist between economic and environmental variables, with particular reference to the water resource in the Ebro Valley (Spain). To that end, we employ the concepts and indicators derived from input-output analysis. Thus, we present a methodology to obtain the key sectors in water consumption and pollution, the forward and backward linkages, the elasticities and the trade-offs between water pollution and the economic variables of income and employment. We obtain the generating sub-systems of water pollution and refine its traditional indicators, thereby allowing the entry of the "anti-pollution sector". This supposes an advance, in that it allows the traditional input-output table to be orientated towards a new approach, one that is the more appropiate for the economic-environmental relationships. The application is made individually for the four regions of the Ebro Valley, as well as for an integrated input-output table for the complete Valley, with our aim being to describe the inter-sectoral productive relations and their impact on water, both within each economy and for the Valley as a whole. Keywords: water economics, water pollution, environmental input-output tables.
Keywords: 330